2009
DOI: 10.1038/emboj.2009.363
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis restricts Arabidopsis KNOLLE syntaxin to the cell division plane during late cytokinesis

Abstract: Cytokinesis represents the final stage of eukaryotic cell division during which the cytoplasm becomes partitioned between daughter cells. The process differs to some extent between animal and plant cells, but proteins of the syntaxin family mediate membrane fusion in the plane of cell division in diverse organisms. How syntaxin localization is kept in check remains elusive. Here, we report that localization of the Arabidopsis KNOLLE syntaxin in the plane of cell division is maintained by sterol-dependent endoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
134
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(139 citation statements)
references
References 54 publications
5
134
0
Order By: Relevance
“…FRAP experiments were performed as described previously (Men et al, 2008;Boutté et al, 2010;Frescatada-Rosa et al, 2014). In brief, FRAP experiments were performed with a Zeiss LSM 780 confocal laser-scanning system mounted on a Zeiss Axio observer Z1 inverted microscope, employing a watercorrected C-Apochromat 403 objective, numerical aperture 1.2 (Zeiss).…”
Section: Frap Analysis Of Fluorescent Fusion Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…FRAP experiments were performed as described previously (Men et al, 2008;Boutté et al, 2010;Frescatada-Rosa et al, 2014). In brief, FRAP experiments were performed with a Zeiss LSM 780 confocal laser-scanning system mounted on a Zeiss Axio observer Z1 inverted microscope, employing a watercorrected C-Apochromat 403 objective, numerical aperture 1.2 (Zeiss).…”
Section: Frap Analysis Of Fluorescent Fusion Proteinsmentioning
confidence: 99%
“…FM4-64 staining was performed as described (Boutté et al, 2010). Briefly, 5-dold seedlings were incubated for 5 min on ice in LM containing 25 mM FM4-64 (Molecular Probes), made from a 25 mM stock in DMSO.…”
Section: Fm4-64 Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, it has been documented by fluorescence microscopy that plasma membranes of plant and fungal cells are laterally compartmented (some examples, see Sutter et al, 2006;Grossmann et al, 2007;Berchtold and Walther, 2009;Lherminier et al, 2009;Raffaele et al, 2009;Boutté et al, 2010;Haney and Long, 2010;Opekarová et al, 2010). Especially the work of S. Mongrand's group (Raffaele et al, 2009) clearly demonstrated that the membrane protein remorin is organized in patches with a size of ;70 nm and that the protein becomes homogenously distributed when the amount of sterols in the membranes is reduced by methyl-b-cyclodextrin.…”
mentioning
confidence: 99%
“…Silencing of the SQUALENE SYNTHASE1 gene compromised the resistance of tobacco (Nicotiana tabacum) to bacterial pathogens because of increased membrane leakage (Wang et al, 2012). Disturbed membrane sterol composition in the Arabidopsis (Arabidopsis thaliana) cyclopropylsterol isomerase1-1 (cpi1-1) mutant affected the polar localization of the PIN2 auxin efflux protein and the cell plate distribution of KNOLLE syntaxin by inhibiting the endocytosis of these proteins (Men et al, 2008;Boutté et al, 2010). Moreover, sterol-enriched plasma membrane microdomains (lipid rafts) have been proposed to act as signaling platforms (Mongrand et al, 2004(Mongrand et al, , 2010Martin et al, 2005).…”
mentioning
confidence: 99%